Pedagogy of Attention: Subverting the Strong Language of Intention in Social Justice Education - Desroches, Sarah J. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
In this paper, I explore the possibility of social justice education as pedagogy of attention rather than simply pedagogy of intention. Drawing on Gert Biesta’s (2010) concept of “strong” education, I begin by explaining how the language of intention in social justice education relies on a discourse in which “in-puts” will result in specific and immediate “out-puts.” In this sense, social justice education can proceed too quickly to action-oriented imperatives. Following this, I take up Jan Masschelein’s (2010) notion of poor pedagogy: pedagogy that requires nothing more than paying attention to argue that creating a space in which the only goal is to pay attention offers the potential of producing a shift in how social justice education proceeds. Pedagogy of attention subverts the primacy of pedagogy of intention by making an important contribution to social justice education, presenting the world in a way that is not contained by the frames (limitations) of what students are told exists, allowing for the possibility of transformation.